2015
DOI: 10.5937/selsem1501009d
|View full text |Cite
|
Sign up to set email alerts
|

New winter triticale species developed at Institute PKB Agroekonomik

Abstract: IzvodU radu su prikazani rezultati ispitivanja prinosa PKB sorti ozimog tritikalea: PKB Vožd i PKB Kardinal u komparaciji sa standardnim sortama: Favorit (Centar za strna žita, Kragujevac) i Odisej (Institut za ratarstvo i povrtarstvo, Novi Sad). Istraživanja su izvedena na Oglednom polju Instituta PKB Agroekonomik, u Padinskoj Skeli, u proizvodnim 2013 i 2014 godini. Utvrđena je visoka značajnost po faktorima: godina i sorta. Najveći prinos ostvarila je sorta PKB Kardinal (9.437,33 kg ha -1 ), a najmanji sort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The results of this study showed that the influence of nitrogen fertilization on the grain yield, components of the yield and the quality of grain, do not depend only on the dose of fertilizers, but also on the climatic conditions, as Janušauskaitė (2013), Ivanova and Kirchev (2014), Djurić et al (2015), Madić et al (2018), Terzić et al (2018 and Đekić et al (2019) had confirmed previously in their researches. (Djekić et al 2012;, as well as many other authors, point out that the high quality of grain and the best triticale yields are obtained in the years with warm bright spring weather conditions and cold summers without excessive precipitation during the grain filling stage, which is in agreement with this study.…”
Section: Resultssupporting
confidence: 70%
“…The results of this study showed that the influence of nitrogen fertilization on the grain yield, components of the yield and the quality of grain, do not depend only on the dose of fertilizers, but also on the climatic conditions, as Janušauskaitė (2013), Ivanova and Kirchev (2014), Djurić et al (2015), Madić et al (2018), Terzić et al (2018 and Đekić et al (2019) had confirmed previously in their researches. (Djekić et al 2012;, as well as many other authors, point out that the high quality of grain and the best triticale yields are obtained in the years with warm bright spring weather conditions and cold summers without excessive precipitation during the grain filling stage, which is in agreement with this study.…”
Section: Resultssupporting
confidence: 70%
“…Effective nitrogen fertilization is essential for producing grains profitably, as well as safeguarding groundwater and surface waters from contamination brought on by nitrate leaching as a result of excessive and insufficient nitrogen application (Todorović and Filipović, 2009;Biberdžić et al, 2012;Babić et al, 2021). Triticale has fewer agro-technical investment requirements than other small grains and is more suited to unfavorable soil and environmental circumstances, which has led to an increase in its use in organic and sustainable agricultural production (Đurić et al, 2015;Rajičić et al, 2020a;Babić et al, 2021). When mineral fertilizers are applied to acidic soils in conjunction with lime and manure, the acidity of the soil is reduced, increasing the yield of farmed crops (Đurić et al, 2015;Rajičić et al, 2020b;Babić et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Triticale has fewer agro-technical investment requirements than other small grains and is more suited to unfavorable soil and environmental circumstances, which has led to an increase in its use in organic and sustainable agricultural production (Đurić et al, 2015;Rajičić et al, 2020a;Babić et al, 2021). When mineral fertilizers are applied to acidic soils in conjunction with lime and manure, the acidity of the soil is reduced, increasing the yield of farmed crops (Đurić et al, 2015;Rajičić et al, 2020b;Babić et al, 2021). Due to the higher cost of mineral, lime, and organic fertilizers as well as the higher cost of producing cereals on acidic soils, it is debatable if such practices are profitable.…”
Section: Introductionmentioning
confidence: 99%
“…By crossing several types of wheat and rye, several types of triticale were obtained (Milovanovic et al, 2014;Camerlengo and Kiszonas, 2023). Great genetic variability is important for the breeding process itself, as well as the way of introducing desirable genes, which, with the selection of genotypes with good performance, results in the creation of varieties of good agronomic and technological quality (Đurić et al, 2015;Kirchev and Georgieva, 2017;Losert et al, 2017). In many countries, including ours (The Republic of Serbia), the areas under triticale, as well as the total production, are constantly increasing from year to year.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%